Investigation of historic, constructive, spatial and pathological aspects regarding the IBC (Instituto Brasileiro do Cafe) in Presidente Prudente, Brazil - Grothues, Laura Karin; Fioriti, Cesar Fabiano [UNESP] (Univ Politecnica Valencia, Editorial Upv, 2019)
In this case study the building of the Brazilian Institute of Coffee (IBC) in Presidente Prudente, Brazil, will be presented. The building was built in the 1940s for the usage of storing coffee. The timber construction is more than 70 years old, which make the shed a historically important heritage to the city. After the revitalization process the building is used as an event center nowadays. The special thing about the architecture of the IBC consists in the construction as a series of wooden latticed porticos. These porticos are still functional and visually appealing, but after so many years of use, they suffer from pathological manifestations. To gain more knowledge about which problems are common in the wooden construction all the porticos were examined in detail. The investigation process revealed, that every portico is affected by at least one of the anomalies studied, even though the degree varies from portico to portico. In addition to the research about the interior of the building, its surrounding was analysed. The urban location and the proximity to other cultural hotspots mean a great chance for the IBC, which should be taken. Comparing the IBC to the cultural center and former coal mine Zollverein in Germany, it becomes clear, that there are several opportunities to reuse a historic building and bind it into city structure. Finally, a critical reflexion of the revitalization process, of the current use and the embedding of the IBC in the environment shows several weaknesses, which could be improved through maintenance and an overall planning concept.
Keywords: revitalization; reuse; preservation; pathological manifestations; timber structures; urban public space